Impact of warning pictorials and size on perceived effectiveness of cigar warning labels in a nationally representative between-subjects experiment - Goldstein, Adam O; Yang, Michelle Z; Jarman, Kristen L; Queen, Tara L; Clark, Sonia A; Ranney, Leah M; Cornacchione Ross, Jennifer; Sheeran, Paschal; Enyioha, Chineme; Thrasher, James F; Jenson, Desmond; Kowitt, Sarah D (BMJ open, 2025)
BackgroundPeople who smoke cigars often have misperceptions about the associated risks, contributing to rises in smoking rates. This study investigates the perceived warning effectiveness (PWE) of health warning labels (HWLs) on cigar packages. We tested the impact of warning type and warning size in the HWLs on PWE and other health outcomes.Data and methodsIn a between-subjects experimental design, participants (n=809) who used little cigars or cigarillos in the past 30 days were randomly assigned to one of four conditions: text-only at 30% size, pictorial+text warning at 30% size, text-only at 50% size and pictorial+text warning at 50% size. In each condition, participants rated six cigarillo HWLs on PWE, self-reported learning, thinking about risks, new knowledge, perceived enjoyment and negative affect. Reactance to the labels was also measured. Data were analysed with mixed-effects models.ResultsPictorial+text cigarillo HWLs were deemed more effective than text-only HWLs in PWE (b=0.34, SE=0.08, p<0.001), self-reported learning (b=0.20, SE=0.08, p=0.01), thinking about risks (b=0.18, SE=0.08, p=0.03) and new knowledge (b=0.34, SE=0.12, p<0.01). They also elicited more negative affect than text-only warnings (b=0.39, SE=0.08, p<0.001). Warning size did not impact outcomes, and neither warning type nor size predicted perceived enjoyment of smoking cigarillos or reactance to the warnings.ConclusionIncluding images with text warning statements for cigarillos can increase PWE. Our findings provide important insights for the US Food and Drug Administration and international regulatory agencies in designing new HWLs for cigars that can more effectively communicate smoking risks, address misinformation and potentially reduce cigar smoking.